Neonatal Sacrococcygeal Fetiform Teratoma Containing Bowel: A Case Report - Toms, Ashley; Govender, Tarlia Rasa; Brisighelli, Giulia; Harrison, Derek (European Journal of Pediatric Surgery Reports, 2024)
A fetiform sacrococcygeal teratoma (homunculus) is a highly differentiated subgroup of mature cystic teratoma that resembles a malformed fetus. These tumors originate at the base of the coccyx and may vary in their intrapelvic and extrapelvic extent and location. It is important to differentiate this anomaly from fetus-in-fetu which has a higher degree of structural organization. A 5-day-old neonate presented with a type II sacrococcygeal fetiform teratoma. The mass contained both cystic and solid components. Upon surgical excision and coccygectomy, fully formed bowel was found inside the mass, as well as bones and other well-defined structures. The tumor was confirmed to be fully excised and no malignant or immature features were found on histopathological examination. The patient was last seen growing well with an alpha-fetoprotein of 3.5 μg/L, 14 months after resection.
Keywords: sacrococcygeal teratoma; fetiform teratoma; fetus-in-fetu; germ cell tumor